Factors Establishing Feasibility of SHGs for Women Entrepreneurship Ventures - Prakash, Ajai; Ruhela, Sandhya (Journal of Commerce and Trade, 2015)
SHGs are essential drivers to enhance financial activities across a number of countries in which women can initiate business activities which can lead to self employment leading to social and economic empowerment. Entrepreneurship is a process of identifying and organising a business venture, sourcing and organising the required resources and taking both the risk and rewards associated with the venture. SHGs are a powerful way under under which women voluntarily create a group with an intent to carry on mutual business operations with the principle of saving and carrying on economic activities for mutual benefit. Women owned businesses are important for any economy of almost all countries. To give thrust to economy of developing countries women entrepreneurship is an essential condition. The ojective of the study is to find out the factors that influence the formation and continuance of Self-help groups for entrepreneurship and study the strengths and limitations of the Self-help groups structure. This study has been conducted on secondary data sources such as research papers, journals, magazines, books and articles. Findings of the study shows that education, innovation, creativity, motivation, low cost, adopting to change, good customer relations, catering to customer needs, desire to succeed and independent operations are main strengths of self help groups. Lack of confidence, lack of education, irregularities in savings, lack of interest of members, non-repayment of loans, lack of marketing abilities among member are some limitations of the self help groups.